Faktor-Faktor yang Mempengaruhi Keputusan Konsumen Dalam Membeli Polis Asuransi Kesehatan - Seri Handayani; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
Health insurance is a service that is engaged in the health sector with a scope of coverage, namely outpatient, inpatient, and emergency services. The purpose of this study was to determine the factors that influence consumer decisions in buying health insurance policies. the most dominant factors or the most influential on consumer purchasing decisions in buying health insurance policies is the product factor which consists of the trust and benefits of the product. keywords: health insurance, consumer behavior